Occupational noise exposure and risk of hypertension in an industrial workforce. Issue 12 (22nd September 2017) - Tessier‐Sherman, Baylah; Galusha, Deron; Cantley, Linda F.; Cullen, Mark R.; Rabinowitz, Peter M.; Neitzel, Richard L.
Abstract : Background: Community noise exposure has been shown to increase the risk of hypertension; however, the relationship between occupational noise exposure and hypertension is less clear. Methods: Using an inception cohort of workers in a specialty metals manufacturing company, we retrospectively assessed occupational noise exposure, hearing acuity, and incident hypertension diagnoses using administrative datasets. Time‐weighted average noise exposure levels were assigned to employees based on their job histories. Cox proportional hazards models were performed to determine the association of noise exposure with risk of incident hypertension. Results: The adjusted hazard ratio (HR) of incident hypertension did not significantly differ between groups by cumulative continuous or categorized noise exposure metric. Conclusion: We found no increased risk of incident hypertension with exposure to occupational noise among workers. Further assessment examining workers' use of hearing protection devices is warranted.